Re-exploring the radio spectrum of Uranus in orbit: science case and digital high-frequency receiver - Lamy, L.; Cecconi, B.; Dekkali, M.; Zarka, P.; Briand, C.; Moncuquet, M.; Pantellini, F.; Griton, L.; Boudouma, A.; Bonnin, X.; Astier, P.-L.; Dias, D.; et al. (My University, 2023)
Among the known planetary magnetospheres, those of Uranus and Neptune display very similar radio environments so that they were referred to as radio twins. Their pioneering exploration by the Voyager 2 Planetary Radio Astronomy (PRA) and Plasma Wave Science (PWS) experiments revealed a variety of electromagnetic radio waves ranging from a few kHz to a few tens of MHz similar to -although more complex than- those of Saturn or the Earth. The asymmetric magnetosphere of Uranus is highly atypical with a large obliquity, magnetic tilt and fast rotation period, so that the magnetosphere undergoes perpetual geometric recon guration. Hereafter, we review the rich zoo of Uranian radio emissions, including the auroral Uranian Kilometric Radiation (UKR) between a few kHz and 1 MHz, the Uranian Electrostatic Discharges (UED) observed up to 40 MHz, and low frequency waves (continuum, plasma wave emissions) at a few kHz. We then emphasize the interest of re-exploring this atypical radio source and present a modern concept of a digital High Frequency Receiver (HFR) in the framework of a Radio and Plasma Wave (RPW) experiment to be proposed to any future NASA/ESA orbital mission toward Uranus. This HFR concept, updated from the heritage of Cassini/RPWS/HFR, STEREO/Waves, Bepi-Colombo/PWI/Sorbet or Solar Orbiter/RPW is aimed at providing a light, robust, low-consumption versatile instrument capable of goniopolarimetric (polarization and direction-finding capabilities) and waveform measurements from a few kHz to ~40MHz, devoted to the study of radio emissions, plasma waves and dust impacts.
Planetary, Solar and Heliospheric Radio Emissions IX
PUBLISHED